Mechanistic understanding of biogeochemical transformations of trace elements in contaminated minewaste materials under reduced conditions - Karna, Ranju Rani (Kansas State University, 2014)
The milling and mining operations of metal ores are one of the major sources of heavy metal contamination at earth’s surface. Due to historic mining activities conducted in the Tri-State mining district, large area of land covered with mine waste, and soils enriched with lead (Pb), zinc (Zn) and cadmium (Cd) remain void of vegetation influencing ecosystem and human health. It has been hypothesized that if these minewaste materials are disposed of in the flooded subsidence pits; metals can be transformed into their sulfide forms under reduced conditions limiting their mobility, and toxicity. These mine waste materials are high in pH, low in organic carbon (OC) and sulfur (S). The objective of this study was to examine the effect of OC and S addition on the biogeochemical transformations of Pb, Zn and Cd in submerged mine waste containing microcosms. Advanced molecular spectroscopic and microbiological techniques were used to obtain a detail, mechanistic, and molecular scale understanding of the effect of natural and stimulated redox conditions on biogeochemical transformation and dynamics of Pb, Zn and Cd essential for designing effective remediation and mitigation strategies. The results obtained from these column studies indicated that Pb, Zn and Cd were effectively immobilized upon medium (119-day) and long-term (252-day) submergence regardless of treatment. The OC plus S treatment enhanced sulfide formation as supported by scanning electron microscopy- energy dispersive X-ray technique, and synchrotron based bulk-, and micro-X-ray fluorescence and absorption spectroscopy analyses. Microbial community structure changed with OC and S addition with the enhancement sulfur reducing bacteria genes (dsrA/B), and decreased metal resistance genes over time. The long-term submergence of existing mine tailings with OC plus S addition reduced trace metals mobility most likely through dissimilatory sulfate reduction under stimulated reduced conditions. Colloidal assisted metal transportation (<1% of both Pb and Cd) occurred during initial submergence. Retention filters are suggested to avoid colloidal metal transport in order to meet the maximum concentration limit for Pb and Cd in surface and groundwater. This research enhances our understanding of the redox processes associated with the sequestration of non-redox sensitive metals through dissimilatory reduction of sulfates in mine waste materials and/or waste water and provides regulators with useful scientific evidence for optimizing remediation goals.
Keywords: Tri-State; Minewaste; Trace element; Transformation; Microarray; Sulfur reducing bacteria; Aerospace Engineering (0538); Biogeochemistry (0425); Environmental Sciences (0768); Soil Sciences (0481)